DAMPAK PANDEMI COVID-19 PADA KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGE - Juwari Juwari (Jurnal Edueco, 2022)
The purpose of this study is to determine and analyze financial performance before and during the Covid-19 pandemic based on Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio, Net Profit Margin, Return on Equity in Food And Beverage Sub-Sector companies. The data analysis method uses a normality test, namely Shapiro Wilk, and a hypothesis test, namely paired t-test samples. The results of the analysis show that there is no significant difference in terms of liquidity ratios, namely the current ratio, quick ratio, debt to assets ratio, solvency ratio, namely debt to equity ratio, and profitability ratio, namely net profit margin and return on equity. Keywords: Financial Performance, Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio, Net Profit Margin, Return on Equity.